Development of CORE model-based student worksheet on trigonometric ratios to facilitate students’ mathematical conceptual understanding - Putri, Salsabila Ivana; Suanto, Elfis; Yuanita, Putri (Jurnal Gantang, 2025)
This research was motivated by the low ability of students to understand mathematical concepts, particularly in the topic of trigonometric ratios. The CORE model was chosen because it encourages active student participation in constructing concepts through systematic stages. The purpose of this study is to develop a valid and practical CORE-based worksheet on trigonometric ratios to support students' conceptual understanding. The development process followed the 4-D model (define, design, development, disseminate). Research data consisted of qualitative input from validators and students, as well as quantitative data from questionnaire scores. Data collection was conducted through interviews and questionnaires using validation sheets and student response instruments. The sample was selected through purposive sampling: 6 students from class XE.1 (Small Group) and 30 students from class XE.3 (Field Test). A worksheet is considered valid and practical if it achieves its values. The results showed that the developed worksheet was very valid (94.31%) based on appearance, content, and construction aspects. It was also very practical, with scores of 97.36% for Small Group and 90.13% for Field Test, assessed based on presentation, ease of use, readability, and time. CORE based worksheets encourage students to actively construct concepts actively actively, thereby facilitating their ability to conceptual understand trigonometric ratios.